Affect labeling and other aspects of emotional experiences in relation to alexithymia following standardized emotion inductions. (April 2018) - Aaron, Rachel V.; Snodgress, Matthew A.; Blain, Scott D.; Park, Sohee
Abstract: Alexithymia is associated with increased risk for mental and physical health disorders but available assessments rely exclusively on self-report. The major aim of the current study was to develop and implement a performance-based task designed to characterize and quantify the relationship between one's description of emotional experience and self-reported alexithymia. Specifically, we examined performance-based measures of affect labeling of one's own emotions, emotional granularity and dialecticism. Healthy participants ( N  = 108) completed the Toronto Alexithymia Scale–20 Item Questionnaire. Participants viewed a series of film clips standardized to elicit discrete emotional states. After each clip, they indicated the emotion they experienced "the most" and rated a list of non-primary emotions, which formed indices of emotional granularity and dialecticism. Alexithymia was associated with increased tendency to report experiencing "no emotion" following evocative film clips, reduced negative emotional granularity and dialecticism of experienced emotions. TAS-20 subscales were each associated with a unique set of emotional correlates. In a healthy population, alexithymia is associated with reduced awareness of emotional states, and reduced dialecticism and granularity of negative (but not positive) emotions. Our performance-based assessment enriches understanding of the mechanisms underlying alexithymia by underscoring the central importance of emotion awareness, negative emotional granularity and dialecticism. Highlights: Alexithymia associated with experiencing 'no emotion' following evocative videos. Alexithymia associated with reduced complexity of negative emotions. Complexity of positive emotions intact in alexithymia. Alexithymia subscales predicted by distinct subsets of emotional variables.